Sero-Surveillance to Monitor the Trend of SARS-CoV-2 Infection Transmission in India: Study Protocol for a Multi Site, Community Based Longitudinal Cohort Study - Nair, Divya; Raju, Reshma; Roy, Sudipto; Dandge, Shailendra; Chethrapilly Purushothaman, Girish Kumar; Jayaraman, Yuvaraj; Kangusamy, Boopathi; Shrivastava, Rahul; Arora, Narendra Kumar; Rose, Winsley; Juvekar, Sanjay; Jammy, Guru Rajesh; et al. (Frontiers in Public Health, 2022)
Introduction Large-scale sero-prevalence studies with representation from all age groups are required to estimate the true burden of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections in the community. Serial serological surveys in fixed cohorts enable study of dynamics of viral transmission and correlates of immune response over time in the context of gradual introduction of COVID-19 vaccines and repeated upsurge of cases during the pandemic. Methods This longitudinal study will involve follow-up of a cohort of 25,000 individuals (5,000 per site) aged 2 years and above recruited from five existing demographic surveillance sites in India. The cohort will be tested for the presence of IgG antibodies against S1/S2 spike protein subunits of SARS-CoV-2 in four rounds; once at baseline and subsequently, at intervals of 4 months for a year between January 2021 and January 2022. Neutralization assays will be carried out in a subset of seropositive samples in each round to quantify the antibody response and to estimate the durability of antibody response. Serial serological surveys will be complemented by fortnightly phone based syndromic surveillance to assess the burden of symptomatic acute febrile illness/ influenza like illness in the same cohort. A bio-repository will also be established to store the serum samples collected in all rounds of serological surveys. Discussion The population based sero-epidemiological studies will help to determine the burden of COVID-19 at the community level in urban and rural Indian populations and guide in monitoring the trends in the transmission of SARS-CoV-2 infection. Risk factors for infection will be identified to inform future control strategies. The serial serological surveys in the same set of participants will help determine the viral transmission dynamics and durability of neutralizing immune response in participants with or without symptomatic COVID infection.